Overstepping the boundaries: notes on intimacy. (2nd September 2017) - Talbot, Emma
ABSTRACT: This article considers intimacy, and the use of personal material to generate artwork and writing. It gives a first-hand account of drawing, in the author's own practice as an artist, as a means to articulate acutely personal life experiences. Looking at both Luce Irigaray's thoughts on intimacy as a singular space where one can meet oneself (rather than simply something shared between two), and ideas surrounding the space of the feminine, this article considers what is at stake when the borders of personal privacy are broken. Using the song lyrics of Joni Mitchell and writing by Anais Nin and Edna O'Brien as references, this article proposes a proximity between approaches to writing the feminine and the practice of drawing/painting. By allying the ways these referents have often been overlooked with attitudes to the feminine, this article defends the import of their output.